The Application of Coronary Contrast Emptying Time in Diagnosing Coronary Slow Flow Phenomenon: A Serial Case Report - Yudhie Tanta; Ali Ghanie; Taufik Indrajaya; Erwin Sukandi; Imran Saleh; Ziske Maritska (Interna Publishing, 2022)
The Coronary Slow Flow Phenomenon doesn't achieve as much attention as its counterpart Coronary Arterial Disease because it is considered a rather benign entity. But now it is proven that coronary slow flow phenomenon can also manifest as an acute coronary syndrome, myocardial ischemia, malignant arrhythmia, and even sudden cardiac death. This entity is usually diagnosed from coronary angiography study when a delayed coronary contrast filling time is found without the presence of significant epicardial narrowing of the related arteries. But, in our center's years of experience, we frequently found cases in which myocardial ischemia or infarction was suggested or proven clinically, on the other hand, angiography study showed no significant epicardial coronary artery narrowing neither delayed coronary contrast filling time. Furthermore, we observed that this group of patients exhibited a rather prolonged coronary contrast emptying time instead. In this serial case report, we presented some of our cases where microvascular disorders were suspected. We demonstrated that not all coronary contrast filling times in ischemic or infarction-related arteries were prolonged, on the other hand, prolongation of coronary contrast emptying time showed a more consistent result.